2022
DOI: 10.1177/17562848221138168
|View full text |Cite
|
Sign up to set email alerts
|

Update on the first-line treatment of Helicobacter pylori infection in areas with high and low clarithromycin resistances

Abstract: Current international consensuses on Helicobacter pylori eradication therapy recommend that only regimens that reliably produce eradication rates of ⩾90% should be used for empirical treatment. The Real-world Practice & Expectation of Asia-Pacific Physicians and Patients in Helicobacter Pylori Eradication Survey also showed that the accepted minimal eradication rate in H. pylori-infected patients was 91%. According to efficacy prediction model, the per-protocol eradication rates of 7-day and 14-day standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…However, its resistance rate is continuously increasing in some regions and countries 34 . As further research and development‐related alternative to compensate for the losing efficacy in therapeutic regimens is hard to accomplish quickly, the WHO recommended that cautious application of CLR in regions with a resistance rate of more than 20% is a likely successful approach 35 . Alessia Savoldi et al assessed the CLR‐resistance rate of H. pylori in all WHO regions 36 .…”
Section: Resistance Profiles and Biomolecular Mechanisms Of Single‐dr...mentioning
confidence: 99%
“…However, its resistance rate is continuously increasing in some regions and countries 34 . As further research and development‐related alternative to compensate for the losing efficacy in therapeutic regimens is hard to accomplish quickly, the WHO recommended that cautious application of CLR in regions with a resistance rate of more than 20% is a likely successful approach 35 . Alessia Savoldi et al assessed the CLR‐resistance rate of H. pylori in all WHO regions 36 .…”
Section: Resistance Profiles and Biomolecular Mechanisms Of Single‐dr...mentioning
confidence: 99%
“…Hsu et al suggest a cutoff for clarithromycin resistance at or below 5 % for the empirical use of PPI-amoxicillin-clarithromycin and base their claim on a recent systematic review 4. However, this review has several relevant limitations:…”
mentioning
confidence: 99%
“…Fourth, it remains implausible from studies included in the analysis of Shih et al 4 that patients harbouring clarithromycin-susceptible strains treated with 7-day triple standard therapy had a higher eradication rate (92.5%) than those receiving 14-day triple standard therapy (eradication rate of 90.2%).…”
mentioning
confidence: 99%
“…In the consensus report, clarithromycin triple therapy is recommended as first-line empirical treatment in areas of low clarithromycin resistance, and low clarithromycin resistance is defined as clarithromycin resistance rate <15%. However, a recent systemic review for randomised controlled trials published between 1 January 2011 and 1 January 2022 showed that the per-protocol eradication rates of 14-day clarithromycin triple therapy for clarithromycin-susceptible strains and clarithromycin-resistant H. pylori strains were 90.2% and 46.2%, respectively 3. The corresponding eradication rates of 7-day clarithromycin triple therapy were 92.5% and 42.9%.…”
mentioning
confidence: 99%
“…The corresponding eradication rates of 7-day clarithromycin triple therapy were 92.5% and 42.9%. According to efficacy prediction model, per-protocol eradication rates of 7-day and 14-day clarithromycin triple therapies fall below 90% when clarithromycin resistance rate is greater than 5% 3. In fact, all the prospective studies in that systemic review demonstrated that per-protocol eradication rates of 7-day and 14-day clarithromycin triple therapies fell below 90% in areas with clarithromycin resistance between 7% and 14% 4 5.…”
mentioning
confidence: 99%